Exploring Preferential Ring-Based Gesture Interaction Across 2D Screen and Spatial Interface Environments - Hoon Yoon; Hojeong Im; Seonha Chung; Taeha Yi (Applied Sciences)
As gesture-based interactions expand across traditional 2D screens and immersive XR platforms, designing intuitive input modalities tailored to specific contexts becomes increasingly essential. This study explores how users cognitively and experientially engage with gesture-based interactions in two distinct environments: a lean-back 2D television interface and an immersive XR spatial environment. A within-subject experimental design was employed, utilizing a gesture-recognizable smart ring to perform tasks using three gesture modalities: (a) Surface-Touch gesture, (b) mid-air gesture, and (c) micro finger-touch gesture. The results revealed clear, context-dependent user preferences; Surface-Touch gestures were preferred in the 2D context due to their controlled and pragmatic nature, whereas mid-air gestures were favored in the XR context for their immersive, intuitive qualities. Interestingly, longer gesture execution times did not consistently reduce user satisfaction, indicating that compatibility between the gesture modality and the interaction environment matters more than efficiency alone. This study concludes that successful gesture-based interface design must carefully consider the contextual alignment, highlighting the nuanced interplay among user expectations, environmental context, and gesture modality. Consequently, these findings provide practical considerations for designing Natural User Interfaces (NUIs) for various interaction contexts.